2023
DOI: 10.1088/1755-1315/1259/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio Char and Amino Acid (Steam) on Growth and Green Yield of Onion (Allium cepa L.) Variety (Karbala)

Ragheed M. Hamza Alsultan,
Wael Fahmi Abdulrahman Al-Shamary,
Mariam Adnan Ibrahim
et al.

Abstract: The experiment was carried out in the vegetable field of Horticulture and Landscape Department / College of Agriculture and Forestry / University of Mosul, during 2021-2022 season to investigate the effect of administration of bio char in three doses (0, 3.5, 7, 10.5 t. Ha-1) and three Concentrations of Amino acid(Steam)(0, 10, 15 ml.L-1)on growth and green yield of onion variety (Karbala) The experiment was designed according to randomized complete block design (RCBD) with three replications. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As the literature reports, an application of biochar to salt-affected soils could increase solubilized inorganic forms, nutrient availability, and uptake which improve soil quality causing enhancement of soil physiochemical properties which reflect positively on the plant physiological and biochemical characteristics [4]. Other studies reported that applying biochar in 7 t ha −1 doses to the soil significantly increased several growth and yield parameters (bulb number, leaves number, bulb diameter, fresh and dry weight of leaves and roots, plant yield, and biological yield) according to experiments developed at the University of Mosul in Iraq [50]. In addition, spraying amino acid (Steam) gave the highest values of plant height, fresh and dry weight of leaves and roots per plant, and diameter of bulb neck [50].…”
Section: Functional Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…As the literature reports, an application of biochar to salt-affected soils could increase solubilized inorganic forms, nutrient availability, and uptake which improve soil quality causing enhancement of soil physiochemical properties which reflect positively on the plant physiological and biochemical characteristics [4]. Other studies reported that applying biochar in 7 t ha −1 doses to the soil significantly increased several growth and yield parameters (bulb number, leaves number, bulb diameter, fresh and dry weight of leaves and roots, plant yield, and biological yield) according to experiments developed at the University of Mosul in Iraq [50]. In addition, spraying amino acid (Steam) gave the highest values of plant height, fresh and dry weight of leaves and roots per plant, and diameter of bulb neck [50].…”
Section: Functional Traitsmentioning
confidence: 97%
“…Other studies reported that applying biochar in 7 t ha −1 doses to the soil significantly increased several growth and yield parameters (bulb number, leaves number, bulb diameter, fresh and dry weight of leaves and roots, plant yield, and biological yield) according to experiments developed at the University of Mosul in Iraq [50]. In addition, spraying amino acid (Steam) gave the highest values of plant height, fresh and dry weight of leaves and roots per plant, and diameter of bulb neck [50]. In an experiment developed in a silt loam soil in Thailand, rice husk and rice straw biochar application increased onion yields by 22% and 35%, respectively, compared with the current farmer practice of using raw rice husk [45].…”
Section: Functional Traitsmentioning
confidence: 97%